Analisis Dampak terhadap Efektivitas Ekonomi dan Inovasi Pembangunan Nasional pada Administrasi Publik di Era Digital - Ni'ma Trirahayu Budiyanto (Universitas 17 Agustus 1945, 2025)
Digital era demands rapid adaptation by public administration to increase economic effectiveness and drive innovation in national development. This study aims to analyze the impact of public administration digitalization on economic effectiveness and national development innovation, as well as to identify inhibiting and supporting factors. The method used is a qualitative approach through a literature review of various secondary sources such as scientific journals, policy reports, and government publications. The results indicate that digitalization through e-government and the integration of technology-based public services have increased bureaucratic efficiency, transparency, and the quality of public services, which in turn strengthens the national economic ecosystem. Digital transformation also encourages policy innovation and cross-sector collaboration in development. However, gaps in digital infrastructure between regions, low digital literacy among officials and the public, and bureaucratic cultural resistance are major obstacles to equitable distribution of these positive impacts. Therefore, optimizing public administration digitalization requires a national strategy oriented toward equity, human resource capacity building, and institutional innovation to strengthen economic competitiveness and achieve sustainable national development.